Online BIST and BIST-based diagnosis of FPGA logic blocks. - Abramovici, M. (IEEE Transactions on VLSI systems)
We present the first online built-in self-test (BIST) and BIST-based diagnosis of programmable logic resources in field-programmable gate arrays (FPGAs). These techniques were implemented and used in a roving self-testing areas (STARs) approach to testing and reconfiguration of FPGAs for fault-tolerant applications. The BIST approach provides complete testing of the programmable logic blocks (PLBs) in the FPGA during normal system operation. The BIST-based diagnosis can identify any group of faulty PLBs, then applies additional diagnostic configurations to identify the faulty look-up table or flip-flop within a faulty PLB. The ability to locate defective modules inside a PLB enables a new form of fault-tolerance that reuses partially defective PLBs in their fault-free modes of operation.